(untitled) (Research, Society and Development, 2022)
Objective: The study was made to identify the influence of spirituality and religiosity by understanding the hospitalized patient`s perception. Method: Qualitative survey founded on the Minayo content analysis. The study was made with 07 participants who have chronical pain, hospitalized in a University Hospital in the State of Parana, Brazil. Individual semi-structure interviews were taken. Results: the study findings show that most of the surveyed individuals were female, average age of 50 years. The predominant religion being Catholicism. The chronical disease being Systemic Arterial Hypertension. Four theme categories were drawn: God, daily strength source; Prayer as a sign of faith and search for comfort, duty and devotion; Religious community as support while facing the disease and the religious institution as a subterfuge for faith; The healthcare professional and the spiritual approach. Conclusion: It was notorious that religiosity/spirituality must be valued when it comes to nursing assistance, as they can be tools to improve the therapeutical process.